Bioactivity enhancement by a ball milling treatment in novel bioactive glass-hydroxyapatite composites produced by spark plasma sintering. Issue 3 (March 2023) - Angioni, Damiano; Orrù, Roberto; Cao, Giacomo; Garroni, Sebastiano; Bellucci, Devis; Cannillo, Valeria
Abstract: Hydroxyapatite (HA) and a lab-made bioactive glass (BGMS10) are combined (50/50 wt%) in this work, where the effect produced by a ball milling (BM) treatment (0–120 min) prior SPS consolidation on the characteristics of the resulting products is investigated. An extraordinary improvement of the apatite-forming ability during in-vitro test on SPS samples (800 °C/70 MPa/2 min) is obtained using the 30 min BMed mixture. Superior Young's Modulus (122 GPa) and Vickers Hardness (675) were also found compared to unmilled samples (95 GPa and 510, respectively). Microstructural changes induced by BM, with 90 nm HA crystallites size in the bulk composite, and the intimate HA/BGMS10 interfaces established, are the factors mainly responsible for such result. When milling was prolonged to 120 min, samples with relatively lower density, mechanical properties, and in-vitro bioactivity, were produced under the same SPS conditions. The formation of crystalline SiO2 during SPS might be responsible for such behaviour.